(untitled) (International journal of artificial intelligence, 2025)
This study examines the econometric and statistical relationship between strategic planning implementation and enterprise performance in Uzbekistan’s construction industry. Using data from “SANEG Construction” RCC for the period 2022–2024, the research evaluates how planning efficiency influences profitability, cost optimization, and overall resource utilization. An econometric model integrating regression, correlation, and variance analysis is applied to assess the quantitative impact of strategic management practices. The findings demonstrate a statistically significant and positive relationship between structured strategic planning and enterprise performance, while also revealing the moderating role of financial risk.